Deltaic Reservoir Partitions and Connectivity - Herman Darman (Berita Sedimentologi, 1999)
A major part of the oil in the world produced from sandstone reservoirs has been from ancient delta systems. In general deltaic sands occur farther down dip than any other type of sand and they have relatively high recovery efficiency. Detail depositional environment study on deltaic reservoirs is important to create a model showing the distribution of reservoir properties that affect fluid flow. This article discussed the geometry and connectivity of deltaic reservoirs.